HARNESSING PHOTOGRAMMETRY FOR WHITEWATER SLALOM COURSES IN NATURAL RIVERBEDS: AN INNOVATIVE APPROACH FOR COURSE DESIGN AND ANALYSIS - Pollert, J.; Strogonov, V. (International archives of the photogrammetry, remote sensing and spatial information sciences., 2023)
Whitewater slalom, a thrilling and challenging water sport, requires carefully designed courses that provide a dynamic and engaging experience for athletes. Traditional methods of designing slalom courses in natural riverbeds have relied on manual measurements and estimations, which can be time-consuming, labour-intensive, and subject to human error. However, with the advent of photogrammetry, a cutting-edge technology that involves the use of aerial or ground-based cameras to capture and process 3D data from images, there is a new frontier in designing and analysing white water slalom courses.This article explores the usage of photogrammetry in the context of white-water slalom course design in natural riverbeds. It highlights how photogrammetry can revolutionize the course design process by providing accurate and detailed 3D models of the riverbed terrain, which can be used for virtual simulations, rapid prototyping, and precise analysis of different design options. The advantages of using photogrammetry include improved accuracy, efficiency, and cost-effectiveness in comparison to traditional methods.The article concludes by discussing the challenges and limitations of using photogrammetry for whitewater slalom course design, including issues related to data acquisition, processing, and accuracy. Despite these challenges, the potential of photogrammetry in revolutionizing the design and analysis of white-water slalom courses in natural riverbeds is immense, and it opens up exciting opportunities for further research, innovation, and advancement in the field of water sports.